2021
DOI: 10.7554/elife.69302
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the relationship between SARS-CoV-2 viral load and infectiousness

Abstract: The relationship between SARS-CoV-2 viral load and infectiousness is poorly known. Using data from a cohort of cases and high-risk contacts, we reconstructed viral load at the time of contact and inferred the probability of infection. The effect of viral load was larger in household contacts than in non-household contacts, with a transmission probability as large as 48% when the viral load was greater than 1010 copies per mL. The transmission probability peaked at symptom onset, with a mean probability of tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 37 publications
(61 reference statements)
7
88
0
Order By: Relevance
“…Measurement of SARS-CoV-2 viral load over the course of acute infection can inform hypotheses about the mechanisms that underlie variation in transmissibility according to variant and vaccination status. 1 …”
mentioning
confidence: 99%
“…Measurement of SARS-CoV-2 viral load over the course of acute infection can inform hypotheses about the mechanisms that underlie variation in transmissibility according to variant and vaccination status. 1 …”
mentioning
confidence: 99%
“…Table 2 presents the results of five identified studies that estimated the association between viral load and the odds of transmission, mainly for the wild type virus and Alpha variant. [18][19][20][21][22] The association for the Delta variant was consistent. 22 The median odds ratio per log 10 increase in viral load in any setting, or within a non-household setting, was 1.33, indicating that, on average, a ten-fold increase in viral load (e.g., from 100,000 copies/mL to 1 million copies/mL) is associated with a 1.33-fold increase in the odds of transmission.…”
Section: Relationship Between Viral Load and Transmissionmentioning
confidence: 89%
“…The only study that assessed the association in a household setting specifically found an odds ratio of 1.77 per log 10 increase in viral load. 19 Since there is less variation in the exposure of contacts in household settings, this stronger association is expected. The median odds ratio per log 10 increase in viral load in any setting, or within a non-household setting, was 1.33, indicating that a ten-fold increase in viral load (e.g., from 100,000 copies/mL to 1 million copies/mL) is associated with a 1.33-fold increase in the odds of transmission, on average.…”
Section: Relationship Between Viral Load and Transmissionmentioning
confidence: 98%
See 2 more Smart Citations